EFFECT OF SUPERVISION OF SUPERVISORY, WORK MOTIVATION AND JOB SATISFACTION ON ELEMENTARY SCHOOL TEACHER PERFORMANCE AT SUMBER AGUNG FIRST GROUP - Sri Sudarmi (Universitas Ahmad Dahlan, 2016)
This study aims to determine the effect of the regulatory supervision, motivation and job satisfaction on the performance of elementary school teachers throughout the cluster I Sumberagung. The population in this study is elementary school teachers throughout Sumberagung groups totaling 87 people, spread in 10 schools. The sampling technique using simple random sampling and test hypotheses using multiple regression analysis (Multiple Regression). The results showed that the regulatory supervision and motivation affect the performance of teachers, but job satisfaction does not affect the performance of teachers.